Catalyst free, visible-light promoted photoaddition reactions between C60 and N-trimethylsilylmethyl-substituted tertiary amines for synthesis of aminomethyl-1, 2-dihydrofullerenes. Issue 3 (18th January 2018) - Lim, Suk Hyun; Cho, Dae Won; Mariano, Patrick S.
Abstract: An efficient and benign method for the preparation of aminomethyl-substituted fullerenes has been developed. The process, involving catalyst free, visible-light irradiation of 10% EtOH-toluene solutions containing fullerene C60 and N -trimethylsilylmethyl-substituted amines by using a 20 W compact fluorescent lamp, leads to formation of aminomethyl-substituted fullerene adducts in a highly efficient manner. The photoaddition reaction takes place via a pathway initiated by visible light absorption by C60, followed by SET from the amine to the triplet excited state of C60 . Ethanol-promoted desilylation of the resulting a minimum radical then generates the corresponding α-amino radical which couples with the C60 radical anion to form the anion precursor of the fullerene adducts. The new approach using visible-light takes place under mild conditions and it does not require the use of photocatalysts. Thus, the method developed in this effort could broadens the range of functionalized fullerene derivatives that can be readily prepared. Graphical abstract: